O clube esportivo feminino : educação e cultura na sociedade cuiabana - Silva, Helleny Nobre da (2020)
This dissertation has as object of research O Clube Esportivo Feminino (Women ́s sport club) opened in the city of Cuiabá in 1928. The importance of this study is relevant mainly because it is an institution founded by a group of women in the city of Cuiabá at the beginning of the 20th century. For this investigation, the following question was elaborated:how the women's sports club was elaborated and organized to promote the education of a social layer of the women of Cuiabáand what is the importance of Zulmira Canavarros' performance in this process?The objective was to understand the educational and cultural significance of the foundation of the WSC, for the society of Cuiabá, mainly for women, through a survey of the social situation in which they were in the period in question.A bibliographic and documentary research was carried out, having as source: books, magazines, newspapers, articles, theses, dissertations, the statute and regiment of the Club. The organization of this research was developed in three chapters; the first chapter sought to understand the social situation of women in their competing representations and in their citizenship rights, based on two main theoretical references: Chartier (1991) and Carvalho (2011). Chapter two discusses the performance of musician Zulmira Canavarros in the WSC, having as main reference the work of Dorileo (1976). Chapter three analyzed the processes of the Club in question, its inauguration, its statute, its internal rules and activities, having its analyses centered on Chartier (1991) and Sanfelice (2007), concluding that the club was an educational and cultural institution, focused on the practice of sports and reading practices, holding cultural festivals, but for a public extremely delimited according to political interests in force in the time in question.